1958
DOI: 10.1139/y58-097
|View full text |Cite
|
Sign up to set email alerts
|

Plant Sterols, Degree of Unsaturation, and Hypocholesterolemic Action of Certain Fats

Abstract: Dietary experiments in which food was supplied in the form of a homogeneous liquid formula ration of definitely known composition have been performed on 171 subjects (159 men and 12 women, university students).During an initial period of 8 days all subjects ate the same ration and then groups of 8 to 12 individuals were given rations varying in respect of the fat moiety for a further 8 days. Plasma cholesterol analyses were performed at day 0, 4, 8, 12, and 16.The results obtained were interpreted as indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1959
1959
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Results obtained in this laboratory (19), in addition to those of other investigators (20)(21)(22)(23)(24), have indicated that partial hydrogenation has little effect on the hypocholesterolemic action of dietary fats. There are,-however, numerous reports (8, 9, 13.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Results obtained in this laboratory (19), in addition to those of other investigators (20)(21)(22)(23)(24), have indicated that partial hydrogenation has little effect on the hypocholesterolemic action of dietary fats. There are,-however, numerous reports (8, 9, 13.…”
supporting
confidence: 53%
“…The reports in the literature do not agree as to whether hydrogenation of a vegetable oil alters its hypocholesterolemic action (8,9,17,20,26,38,39). Since the process of hydrogenation, as normally used in the preparation of edible fats, results in the conversion of polyunsaturated to monounsaturated fatty acids and in the formation of some isomeric unsaturated fatty acids, either one or both types of change might possibly modify the plasma cholesterol response.…”
Section: Methodsmentioning
confidence: 99%
“…One year later, researchers reported that within the context of a 35% butterfat diet, there was no significant difference between supplemental corn oil and hydrogenated corn oil. 2 Between 1960 and 1990, numerous additional studies were published with inconsistent results. This variability is likely attributable to differences in the background diets, starting fatty acid profile of the test oil, differences in the degree and type of hydrogenation, and less-than-optimal comparison fats.…”
mentioning
confidence: 99%
“…This paper describes experiments using these cholesterol-free diets with HCO to induce atheroma and to test their regression when the HCO was replaced by SO. In human studies, Beveridge et al 2 reported that the unusual hypocholesteremic effect of corn oil is due to its relatively high sitosterol eontent. We were interested, therefore, to test the value of both SO and SO plus /?-sitosterol (S:S) to regress atheroma in rabbits.…”
mentioning
confidence: 99%